Boundary effects on the local density of states of one-dimensional Mott insulators and charge density wave states - Schuricht, D; Essler, F; Jaefari, A; Fradkin, E (2011)
We determine the local density of states (LDOS) for spin-gapped one-dimensional charge density wave (CDW) states and Mott insulators in the presence of a hard-wall boundary. We calculate the boundary contribution to the single-particle Green function in the low-energy limit using field theory techniques and analyze it in terms of its Fourier transform in both time and space. The boundary LDOS in the CDW case exhibits a singularity at momentum 2kF, which is indicative of the pinning of the CDW order at the impurity. We further observe several dispersing features at frequencies above the spin gap, which provide a characteristic signature of spin-charge separation. This demonstrates that the boundary LDOS can be used to infer properties of the underlying bulk system. In the presence of a boundary magnetic field, midgap states localized at the boundary emerge. We investigate the signature of such bound states in the LDOS. We discuss the implications of our results for scanning tunneling microscopy experiments on quasi-one-dimensional systems such as two-leg ladder materials like Sr14Cu 24O41. By exchanging the roles of charge and spin sectors, all our results directly carry over to the case of one-dimensional Mott insulators.© 2011 The American Physical Society.